No causal association between tea consumption and 7 cardiovascular disorders: A two-sample Mendelian randomization study - Cai, Dongsheng; Chen, Jun; Wu, Yuteng; Jiang, Chenyang (Frontiers in Genetics, 2022)
Abstract Background: Previous studies have reported inconsistent results on the causal association between habitual tea consumption and the risk of cardiovascular disease (CVD). This study aims to determine the association between habitual tea intake and CVD using two-sample Mendelian randomization (MR) analysis. Methods: The genetically predicted causation between tea consumption and 7 common cardiovascular diseases (atrial fibrillation, hypertension, acute myocardial infarction, coronary atherosclerosis, peripheral vascular disease, angina, and heart failure) was evaluated using the MR analysis model. We performed a total of 9 MR analysis methods to analyze the final results. The IVW method was used as the primary outcome. The other MR analysis method (simple mode, weighted mode, simple median, weighted median, penalized weighted median, MR Egger, and MR-Egger (bootstrap)) were performed as the complement to IVW. Also, the robustness of the MR analysis results was assessed using a leave-one-out analysis. Results: The IVW analysis methods indicated that there is no causal association between tea consumption and risk of CVD (AF: OR, 0.997, 95% CI, 0.992-1.0001, P=0.142; hypertension: OR, 0.976, 95% CI, 0.937-1.017, P=0.242; AMI: OR, 0.996, 95% CI, 0.991-1.000, P=0.077; CA: OR, 1.001, 95% CI, 0.993-1.009, P=0.854; PVD: OR, 1.002, 95% CI, 1.000-1.005, P=0.096; angina: OR, 0.999, 95% CI, 0.993-1.006, P=0.818; HF: OR, 0.999, 95% CI, 0.996-1.002, P=0.338). The other MR analysis method and further leave-one-out sensitivity analysis suggested the results were robust. Conclusion: This MR study indicated that there was no genetically predicted causal association between habitual tea intake and the risk of CVD.